The Influence of Emotional Intelligence and Perception Organizational Climate on Teacher Performance - Nurul Furqon; Frans Sudirja (International Forum of Researchers and Lecturers, 2023)
This research aims to get empirical answers about (1) emotional intelligence on performance, (2) perceptions of organizational climate on performance, (3) emotional intelligence and perceptions of organizational climate on performance. This research was conducted at the SMK Negeri 2 Demak school with 50 teachers as respondents. This research method is a survey with a regression approach. Based on data processing and research results, it was found: (1) There is an influence of emotional intelligence on teacher performance. (2) There is an influence of organizational climate perceptions on teacher performance. (3) There is a joint influence of emotional intelligence and perceptions of organizational climate on teacher performance. These two variables have a positive and significant influence on improving teacher performance.